Splenic angiomatoid nodular transformation in child with inflammatory pseudotumor-like areas - Monika Vyas; Mahesh Deshmukh; Tanuja Shet; Nirmala Jambhekar (Indian Journal of Pathology and Microbiology, 2011)
Reports of sclerosing angiomatoid transformation (SANT) in the pediatric age group are rare. We present a case of SANT in an 11-year-old child with a history of trauma presenting with rapidly growing splenic lesion since 2 months. A partial splenectomy revealed a well-demarcated nodular lesion 5 × 4 × 4 cm with central area of fibrosis. Most part of the lesion showed ill-defined nodules or diffuse areas of plump epithelioid appearing endothelial units that marked with CD31, but the internodular stroma was inflammatory pseudotumor (IPT)-like with a mitotic count of 1-2/10 hpf. The angiomatoid nodules were diffusely positive for CD31, CD163, and CD68; however, they were negative for CD34, CD30, smooth muscle actin, and CD8. Epstein-Barr virus-encoded RNA in situ hybridization (EBER-ISH) was negative. The MIB1 labeling was fairly high in the IPT area but low in the angiomatoid areas. After the diagnosis of SANT, the patient has had an uneventful follow-up for more than 3 years since surgery. The morphologic findings in the case being discussed reaffirm the finding that SANT may have an IPT component and it can be seen even in pediatric age group.